Existentialism in the Film Sang Kiai and the Relevance of Pancasila Values for Generation Z in the Digital Era - Wajihuddin Wajihuddin; Romdhi Fatkhur Rozi; Fina Zahra (Faculty of Humanities, Universitas Jenderal Soedirman, 2026)
Abstract: This study analyzes the existentialist dimensions in the film Sang Kiai and examines their relevance to Pancasila values for Generation Z in the digital era. It explores how existential values such as freedom, responsibility, and authenticity are represented through the character of KH. Hasyim Asy’ari and how these values can be internalized by Generation Z amid moral challenges and the dynamics of digital information. This research employs a qualitative descriptive approach using Jean-Paul Sartre’s existentialist philosophy as the main analytical framework. The analysis is conducted through narrative examination based on Syd Field’s three-act structure setup, confrontation, and resolution to reveal the philosophical meanings embedded in the storyline and character actions. Data are derived from scene observations, dialogue transcripts, and the socio-historical context of the film, which depicts the struggle of religious leaders in defending national independence and moral values. The findings show that Sang Kiai embodies the spirit of existentialism through the conscious and responsible choices of the main character, who embraces struggle and sacrifice as expressions of authentic freedom. These values are consistent with the principles of Pancasila, particularly belief in the One and Only God, just and civilized humanity, and the unity of Indonesia. The film also reflects moral and spiritual conflicts that resonate with Generation Z, who often face identity crises, value relativism, and post-truth digital culture. This study contributes originality by integrating Sartrean existentialism with Pancasila through Indonesian cinema, highlighting film as a powerful medium for character education and philosophical reflection in the digital age.